Pelatihan Satu Guru Satu Aplikasi Pembelajaran bagi Guru SD Lhoksmawe - Sakdiah, Halimatus; Muliani, Muliani; Lukman, Isna Rezkia (Universitas Nusantara PGRI Kediri, 2022)
The 21st century requires teachers to have skills in utilizing information and communication technology (ICT) in learning. Currently, Android is one of the right media choices in learning in this digital era. This activity aims to train elementary school teachers in improving their ability to use ICT and guide elementary school teachers to create android-based media in learning. Implementation of activities using the method of Direct Instruction, Workshop and Field Guidance. After the activity ended, a closed questionnaire was distributed to find out the results of the activity. The results obtained were an increase in the understanding of ICT for elementary school teachers after this activity was carried out, besides that the teacher was also able to create an Android-based learning application. During the implementation of the activity, the teacher looks enthusiastic and enthusiastic in making applications.